Dividing and conquering the fastest–growing genus: Towards a natural sectional classification of the mega–diverse genus Begonia (Begoniaceae). Issue 2 (25th January 2018) - Moonlight, Peter W.; Ardi, Wisnu H.; Padilla, Luzmila Arroyo; Chung, Kuo-Fang; Fuller, Daniel; Girmansyah, Deden; Hollands, Ruth; Jara-Muñoz, Adolfo; Kiew, Ruth; Leong, Wai-Chao; Liu, Yan; Mahardika, Adi; et al.
Abstract: The pantropical genus Begonia is the sixth–largest genus of flowering plants, including 1870 species. The sections of Begonia are used frequently as analogues to genera in other families but, despite their taxonomic utility, few of the current sections have been examined in the light of molecular phylogenetic analyses. We present herein the largest, most representative phylogeny of Begonia published to date and a subsequent provisional sectional classification of the genus. We utilised three plastid markers for 574 species and 809 accessions of Begonia and used Hillebrandia as an outgroup to produce a dated phylogeny. The relationships between some species and sections are poorly resolved, but many sections and deeper nodes receive strong support. We recognise 70 sections of Begonia including 5 new sections: Astrothrix, Ephemera, Jackia, Kollmannia, and Stellandrae; 4 sections are reinstated from synonymy: Australes, Exalabegonia, Latistigma and Pereira; and 5 sections are newly synonymised. The new sectional classification is discussed with reference to identifying characters and previous classifications.